Identifying levers for change in UK grazing livestock systems - Norton, Lisa R.; Bruce, Ann; Chapman, Pippa J.; Lamprinopoulou, Chrysa; Rothwell, Shane A.; Smith, Laurence G. (Frontiers in Sustainable Food Systems, 2024)
There is an urgent need for transformational change in global and UK agriculture. Current practices undermine the long-term future of farming and impoverish ecosystems in the UK and elsewhere. However, change is not happening at the scale and pace which is needed. Work by David Abson, drawing on ideas by Donella Meadows, explored this failure of progress and proposed a research agenda focused on transformational leverage points which influence sustainability. These points are centred on three realms of leverage: reconnecting people to nature, restructuring institutions and rethinking how knowledge is created and used in pursuit of sustainability. In this paper, these ideas are explored through a combined researcher /stakeholder workshop focused on transformational change in UK livestock systems. Workshop participants were asked to discuss and identify potential levers of change under the three realms identified by Abson. The multiplicity of levers identified and the interactions across realms emphasise the need for new kinds of knowledge creation which are highly transdisciplinary, as well as emphasising the complexity of levers which are likely to play a role in the transformation of livestock food systems in the UK and elsewhere.